AN INVESTIGATION INTO THE CHALLENGE OF ANALYZING A PARALLEL CORPUS PRISM IN THE TRANSLATION OF O'TKIR HASHIMOV'S "WORLD AFFAIRS" - Karimov Rustam Abdurasulovich; Tursunova Markhabo Rakhmonovna (Journals Park Publishing, 2024)
This article talks about corpus linguistics, particularly parallel corpus, which is currently one of the most developed fields in world linguistics. The literary text and its translated text in another language contain ideas about the difficulties that arise in the translation process. In particular, changes in the delivery of the original to readers of other languages in the source language and translation texts are covered in detail.
Keywords: Corpus Linguistics, Parallel Corpus Texts (PKM) Source Language (MT), Translation Language (TT) parallel corpus of scientific texts, parallel corpus of media texts, parallel corpus of artistic texts.